Status Pencemaran Sungai Kapuas Kalimantan Barat - ANGGRAINI, IKA MUTHYA; Parabi, Arif; Widodo, Muji Listyo (Fakultas Teknik Universitas Panca Bhakti, 2023)
The Kapuas River Basin (DAS) has great benefits for the community, especially for clean water needs. The community's need for water starts from the need for drinking water to the need for sanitation. But along the flow of the Kapuas River has experienced pollution. To prevent and improve river water quality, it is necessary to test the water quality in the Kapuas River area and find out the causes of pollution in the research location. This research was conducted in Sintang City as the upstream watershed and Pontianak City as the downstream watershed. Determination of water quality status is carried out using the STORET method. The results obtained, the water of the Kapuas River in the city of Pontianak is classified as heavily polluted. Meanwhile, the Kapuas River water in Sintang City is classified as moderately-severely polluted. The source of the pollutant comes from domestic waste. Efforts to prevent and improve water quality can be carried out by educating the local community regarding water quality and building a Communal WWTP to treat this waste.